2013
DOI: 10.3109/13880209.2013.803579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lycopene on oxidative stress induced duringd-galactosamine/lipopolysaccharide-sensitized liver injury in rats

Abstract: Context: Lycopene is a phytonutrient under considerable investigation for its antioxidant benefits in treating diseases like cancer, cardiovascular diseases, osteoporosis and diabetes. Objective: This study explores the effect of lycopene against oxidative damage during experimental hepatitis, induced by D-galactosamine/lipopolysaccharide (D-GalN/LPS). Materials and methods: Experimental rats were pretreated with lycopene intraperitoneally for 6 d (10 mg/kg body weight/day) and then induced by D-GalN/LPS. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 57 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…LPS/GalN-induced liver injury is characterized by elevated ROS and MDA levels in liver tissues [28]. In this study, our results showed that ADH significantly inhibited LPS/GalN-induced ROS and MDA production in liver tissues.…”
Section: Discussionsupporting
confidence: 55%
“…LPS/GalN-induced liver injury is characterized by elevated ROS and MDA levels in liver tissues [28]. In this study, our results showed that ADH significantly inhibited LPS/GalN-induced ROS and MDA production in liver tissues.…”
Section: Discussionsupporting
confidence: 55%
“…In another study, GST activity showed a significant decrease after Cyanobacterium LPS treatment in zebra fish [37). Similarly, the activity of hepatic GST showed a significant decline when galactosamine /lipopolysaccharide were injected to rats [38].…”
Section: Discussionmentioning
confidence: 89%
“…It improved the enzymatic antioxidants levels (i.e., CAT, GPx, SOD, and GSTs) as well as non-enzymatic antioxidants (i.e., vitamin C and E, and GHS). Moreover, lycopene reduced the high level of lipid peroxides and decreased the DNA strand breaks [130]. Additionally, d-Gal/LPS could induce hepatitis in experimental rats, and lycopene significantly reduced the lipid metabolizing enzymatic activity (i.e., LPL, lecithin-cholesterol acyltransferase (LCAT), hepatic triglyceride lipase (HTGL), and increase in the HDL level [131]).…”
Section: Hepatoprotectivementioning
confidence: 99%